Endothelial Dysfunction, Erectile Dysfunction and Phosphodiesterase 5 Inhibitors. An Update of the Current Data and Future Perspectives - Angelis Konstantinopoulos; Konstantinos Giannitsas; Spiros Raptis; Petros Perimenis (AboutScience Srl, 2007)
Endothelial dysfunction is a pathological entity that multiply affects the health status. Erectile dysfunction is being recognized as a condition that is strongly interrelated with endothelial dysfunction, being a vascular event itself. Oral pharmacotherapy for erectile dysfunction has provided us with a new armamentarium on this condition. Phosphodiesterase 5 inhibitors have been investigated and proved useful in clinical practice for erectile dysfunction but in addition to this, the results seem promising of a beneficial effect on endothelial dysfunction, as well.